Psoriasis and sexuality: Patients express their feelings - Romain Salle; Bruno Halioua; Gaëlle Le Fur; Roberte Aubert; Jason Shourick; Charles Taieb (Wiley, 2023)
Abstract Background In France, psoriasis is a chronic inflammatory skin disease. For several years now, particular attention has been given to the quality of life (Qol) of psoriasis patients. Sexual dysfunction (SD) defined as not wanting or enjoying sexual experience is an important component of Qol. Psoriasis through its physical symptoms and psychological consequences can thus be responsible for SD. Method The survey participants were recruited through the national psoriasis dermatitis patient association. Result 41% (577) patients reported having SD related to their psoriasis. Women reported significantly more SD than men (387 [44.7%] vs. 190 [35%], p < 0.001). For 396 (28.1%) patients SD due to their psoriasis manifested as a reduction in the frequency of sexual activity, for 207 (14.7%) as change in their sexual practice, and for 284 (27.4%) as an absence of sexual activity without significant difference between women and men. The main consequence of sexual difficulties for patients was loss of self‐confidence in 627 (44.5%) cases, guilt in 209 (14.8%) cases, couple life impairment in 214 (15.2%) cases, isolation in 260 (18.5%) cases and frustration. Discussion In this study investigating SD related to psoriasis, we found that the disease impact sexual relations of 41% of patients of both gender. The main causes of SD were both physical alone and psychological alone, in the same proportions. The physical symptoms of psoriasis are therefore not the only ones responsible for the sexual discomfort reported from patients in their sexual relations. This may be due to a discomfort of the patient or the physician when talking about sexuality because they can't find the terms to talk about this subject often considered taboo and the age or gender difference. This aspect of the disease should be considered by physicians who care for patients with psoriasis, especially dermatologists. Finally, other strategies should be implemented, such as patient talk groups, referral guides or personalised therapeutic education.